স্মৃতিকথা : একটি অজানা মেয়ে - রহমান, জওশন আরা (ঢাকা : নবযুগ প্রকাশনী, 2010)
Autobiography of a woman social worker from Bangladesh.
Translation of Jowshan Ara Rahman's autobiography, Smritikatha : ekti ajana meye"--Editor's note.
Complimentary copy
Keywords: Rahman, Jowshan Ara; Women social workers -- Bangladesh; Women social workers -- Bangladesh -- Biography